The UN Committee on the Rights of the Child and Refugees: One NGO’s Experience with the Reporting Process - Clark, Tom (Refuge: Canada’s Journal on Refugees, 1996)
During 1994 and 1995, the InterChurch Committee for Refugees (ICCR) developed a brief to the UN Committee on the Rights of the Child. The brief was to assist the Committee in its examination of Canada’s first report required under the Convention on the Rights of the Child. This article describes the brief, the process ICCR entered into, and the resulting "Report Card" from the UN Committee. Some follow-up work is described briefly.